The Influence of Attraction, Amenity, Health Protocol on Tourist Destinations Re-Visit Interest During The Covid-19 Pandemic - Gian Diva Bayu Krisdamulti; Mar'atul Fahimah (INCOME: Innovation of Economics and Management, 2021)
The purpose of the research is to identify the effect of the tourism components is tourist attraction, amenities, and health protocol during pandemic covid-19 at the Banyu Mili tourist destination in Wonosalam Jombang. This research used a quantitative descriptive approach. This research used descriptive analysis and multiple linear regression analysis.. The sampling technique used in this research is non probability sampling with Purposive Sampling approach. The sample in this research were the visitors of Banyu Mili tourist destination in Jombang city with 103 respondents. Based on the T test results, it has known that tourist attractions has positive and significant effect towards interest to revisit in Banyu Mili, while accessibilities, amenities, ancillary service and health protocol have no significant effect on the tourists' revisiting interest. Based on research result that tourist attraction has the most dominant influence on the interest in revisiting tourist. The better a tourist attraction have, the bigger tourists' revisiting interest will be at Banyu MIli Wonosalam Jombang.